Mechanical and bioactive properties of mullite reinforced pseudowollastonite biocomposite - Farah ‘Atiqah Abdul Azam,; Roslinda Shamsudin,; Ng, Min Hwei; Zalita Zainuddin,; Muhammad Azmi Abdul Hamid,; Rashita Abdul Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Bioactive composites consist of pseudowollastonite and mullite synthesized from natural resources was developed for bone implant applications. To realize such applications, a mechanical test of these composites and in vitro bioactivity in SBF solution were studied. The present paper reports pseudowollastonite synthesized from the rice husk ash and limestone reinforced with 10, 20 and 30 wt. % of mullite. Influence of sintering temperature, phase composition, morphology towards mechanical properties of various pseudowollastonite-mullite (PSW-M) composites was examined prior to the bioactivity test. It was found that pseudowollastonite with the addition of 20 wt. % of mullite sintered at 1150°C gave the best result for diametral tensile strength (DTS) and hardness with the value of 8.8 ± 0.15 MPa and 3.79 ± 0.13 GPa, respectively. The obvious increment in the mechanical strength was due to the formation of liquid phase CaAl2O3 during sintering at 1150°C. In addition, the formation of fibrous apatite (HA) layer of amorphous calcium phosphate (ACP) with Ca/P ratio 1.8 on PSW20M sample confirmed the good bioactivity of the composite.